Shape recoverable, Au nanoparticles loaded nanocellulose foams as a recyclable catalyst for the dynamic and batch discoloration of dyes. (15th April 2021) - Alle, Madhusudhan; Bandi, Rajkumar; Sharma, Garima; Lee, Seung-Hwan; Kim, Jin-Chul
Highlights: Sustainable production of AuNPs@TOCNF nanohybrid without additional reducing agent. Microwave-assisted ultrafast synthesis (30 s) of AuNPs@TOCNF nanohybrid. Highly porous and shape recoverable foam. Batch and dynamic discoloration of dye pollutants. Easy recovery and reusability for up to five cycles. Abstract: An environmental benign in-situ formation and growth of gold nanoparticles (AuNPs) on TEMPO-oxidized cellulose nanofibrils (TOCNF) is reported here. With the active functional groups (aldehyde and carboxyl), TOCNF served as a synchronized reducing and supporting agent for the formation of AuNPs. The entire synthesis process was completed within 30 s under microwave irradiation and regarded as ultra-fast. As obtained AuNPs@TOCNF nanohybrid suspension was freeze-dried to form strong water-activated shape recovery 3D foam. Internal morphology and porosity of the foam were studied by SEM and BET. AuNPs@TOCNF foams exhibited excellent catalytic activity for the discoloration of cationic and anionic dyes in batch and dynamic column processes. The spent foams can be easily recovered and reused up to five cycles with more than 98 % efficiency. During the catalytic processes, no obvious deterioration of the foam structure was observed. Practical applicability of the nanocatalyst was evaluated by treating spiked sea water sample.